On representations of a general solution in the theory of micropolar thermoelasticity without energy dissipation - Giordano, P.; Svanadze, M.; Zampoli, V. (Український математичний журнал, 2007)
In the present paper, the linear theory of micropolar thermoelasticity without energy dissipation is considered. This work is organized as follows: Section 2 is devoted to basic equations for micropolar thermoelastic materials, supposed to be isotropic and homogeneous, and to assumptions on constitutive constants. In Section 3, some theorems related to representations of a general solution are studied. Розглянуто лінійну тєорію мікрополярної термоеластичності без розсіювання енергії. Статтю побудовано таким чином. Другий пункт присвячено базовим рівнянням для мікрополярних термоеластичних матеріалів, які вважаються ізотропними та однорідними, та припущенням щодо основних констант. У третьому пункті доведено деякі теореми про зображення загального розв'язку.